2017
DOI: 10.1093/mnras/stx3032
|View full text |Cite
|
Sign up to set email alerts
|

Detection of non-thermal emission from the massive protostellar jet HH80-81 at low radio frequencies using GMRT

Abstract: Low radio frequencies are favourable for the identification of emission from non-thermal processes such as synchrotron emission. The massive protostellar jet associated with IRAS 18162-2048 (also known as the HH80-81 system) has been imaged at low radio frequencies: 325, 610 and 1300 MHz, using the Giant Metrewave Radio Telescope, India. This is the first instance of detection of non-thermal emission from a massive protostellar jet at such low radio frequencies. The central region displays an elongated structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
(68 reference statements)
1
29
1
Order By: Relevance
“…6). Very recent GMRT observations of HH 80-81 (Vig et al 2018) at 325 and 610 MHz found negative spectral indices steeper than previous studies at higher frequencies. This has been interpreted as indicating that an important free-free contribution is present at high frequencies even in the non-thermal radio knots.…”
Section: Dg Taucontrasting
confidence: 54%
“…6). Very recent GMRT observations of HH 80-81 (Vig et al 2018) at 325 and 610 MHz found negative spectral indices steeper than previous studies at higher frequencies. This has been interpreted as indicating that an important free-free contribution is present at high frequencies even in the non-thermal radio knots.…”
Section: Dg Taucontrasting
confidence: 54%
“…One possible interpretation is that this emission could be due to inverse Compton scattering (IC) of thermal infrared from the ambient cloud, produced by relativistic particles accelerated in the reverse shock, or present in the molecular cloud (e.g. Vig et al 2018). However, to identify the processes that can produce this radiation, a deeper and detailed study is required, using higher sensitivity X-ray images.…”
Section: Hard X-raysmentioning
confidence: 99%
“…Despite being located at large distances from the protostar, HH objects also seem to present a non-thermal component of radio emission. This can be inferred from the detection of very negative spectral indices (α = −0.3 a −0.7; e.g., Marti et al 1993, Vig et al 2018 measured in low angular resolution observations. Kinematic studies of HH 80, HH 81, and HH 80N (hereafter HH 80/81/80N), reveal proper motions of ∼200-400 km s −1 (Masqué et al 2015, Heathcote et al 1998, while the velocity of the jet material is about 1000 km s −1 (Marti et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This acceleration mechanism is ubiquitous in sources with supersonic outflows, such as supernovae remnants (e.g. Dubner & Giacani 2015), Herbig-Haro objects (Rodríguez-Kamenetzky et al 2019), proto-stellar jets (Vig et al 2018), compact young stellar clusters (Yang et al 2018), and microquasars (Mirabel & Rodríguez 1994). In OB and WR systems, the detection of synchrotron emission is strongly correlated with binarity (Dougherty & Williams 2000;De Becker et al 2006).…”
Section: Introductionmentioning
confidence: 98%